'Boundary': mapping and visualizing climatically changed landscapes at Kaskawulsh Glacier and Kluane Lake, Yukon. Issue 3 (20th November 2019) - Shugar, D. H.; Colorado, K. A.; Clague, J. J.; Willis, M. J.; Best, J. L.
ABSTRACT: This paper describes a collaboration between a visual artist and geoscientists, who together viewed the same rugged, high mountain landscape through different, yet complementary, lenses. We pair scientific mapping and historic comparative photography with a series of site-specific sculptural installations to interpret the dramatic geological changes that occurred at Kaskawulsh Glacier, Yukon, in the spring of 2016. In the summer of that year, artist K.A. Colorado accompanied geoscientists D.H. Shugar, J.J. Clague, and J.L. Best to the terminus of Kaskawulsh Glacier, as well as Kluane Lake downstream of the glacier, to document the landscape changes that occurred earlier in the year. The Boundary images were created as on-site, three-dimensional, artistic interpretations of the markedly changed boundaries that occurred as a result of climate-induced glacier retreat and the sudden subcontinental-scale reorganization of drainage. Both the scientific study conducted by the geomorphologists and the art installations created by the artist were performed simultaneously. The Boundary installation art project, together with satellite imagery and historical photographs, conveys the death of Slims River as a result of climate change.